2008
DOI: 10.2460/ajvr.69.6.737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of head-down positioning on regional central nervous system perfusion in isoflurane-anesthetized horses

Abstract: Head-down positioning increased heart-brain hydrostatic gradients in isoflurane-anesthetized horses, thereby decreasing cerebral blood flow and, to a greater extent, increasing ICP. During anesthesia, CNS regions with low blood flows in horses may be predisposed to ischemic injury induced by high ICP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
4
17
0
3
Order By: Relevance
“…The aetiology of spinal cord ischaemia has not been elucidated and there are no recommended strategies for its prevention. Suggested initiating causes have included stretch ischaemia of the spinal cord during dorsal recumbency (possibly exacerbated by the haemodynamic consequences of dorsal recumbency and the associated increases in intraand peri-spinal cord cerebrospinal fluid pressure), verminous arteritis, embolism (thrombo-, fibrocartilagenous or bone marrow), and vitamin E or selenium deficiency (Taylor et al 1977;Schatzmann et al 1979;Blakemore et al 1984;Zink 1985;Brearley et al 1986;Fuentealba et al 1991;Stolk et al 1991;Lerche et al 1993;Gruys et al 1994;Jackson et al 1995;Lam et al 1995;Raidal et al 1997;Joubert et al 2005;Brosnan et al 2008;Ragle et al 2011). It is difficult to explain why CEPEF-3 (Johnston et al 2004) suggested that isoflurane was associated with more of these cases than halothane, although their dissimilar effects on systemic vascular resistance and myocardial contractility may be relevant (Grosenbaugh & Muir 1998;Durongphongtorn et al 2006).…”
Section: Spinal Cord Malacia/post-anaesthesia Neuropathiesmentioning
confidence: 99%
“…The aetiology of spinal cord ischaemia has not been elucidated and there are no recommended strategies for its prevention. Suggested initiating causes have included stretch ischaemia of the spinal cord during dorsal recumbency (possibly exacerbated by the haemodynamic consequences of dorsal recumbency and the associated increases in intraand peri-spinal cord cerebrospinal fluid pressure), verminous arteritis, embolism (thrombo-, fibrocartilagenous or bone marrow), and vitamin E or selenium deficiency (Taylor et al 1977;Schatzmann et al 1979;Blakemore et al 1984;Zink 1985;Brearley et al 1986;Fuentealba et al 1991;Stolk et al 1991;Lerche et al 1993;Gruys et al 1994;Jackson et al 1995;Lam et al 1995;Raidal et al 1997;Joubert et al 2005;Brosnan et al 2008;Ragle et al 2011). It is difficult to explain why CEPEF-3 (Johnston et al 2004) suggested that isoflurane was associated with more of these cases than halothane, although their dissimilar effects on systemic vascular resistance and myocardial contractility may be relevant (Grosenbaugh & Muir 1998;Durongphongtorn et al 2006).…”
Section: Spinal Cord Malacia/post-anaesthesia Neuropathiesmentioning
confidence: 99%
“…Intracranial strain‐gauge pressure‐sensing devices consisting of a miniaturized silicon transducer enclosed in a titanium case and implanted in the tip of a flexible nylon‐covered cable have been described for measurement of ICP in both awake and anesthetized horses under a variety of conditions . Their flexibility, low profile design and ease of use mean they are more easily operated, less prone to breakage and better tolerated in the conscious animal.…”
Section: Introductionmentioning
confidence: 99%
“…The vessel rich group (VRG) of tissues that receive high mass-specific blood flow include sites within the central nervous system (CNS) responsible for anesthetic actions. 18 As a result, the partial pressure of anesthetic within the VRG is in delayed equilibrium with the partial pressure of anesthetic in the alveoli. Factors that promote increased anesthetic uptake from the alveoli, namely high cardiac output and high λ B:G , oppose the rate of partial pressure increase of anesthetic in the alveoli, and thus delay the partial pressure increase in the CNS.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…18,8587 In many species, inhaled anesthetics interfere with compensatory vasomotor responses to changes in cerebral perfusion pressure, resulting in either uncontrolled excess or inadequate tissue perfusion. Surprisingly, over a wide range of perfusion pressures, isoflurane-anesthetized horses maintain regional cerebral blood flow relatively constant, albeit at a low flow that may still place animals at risk for tissue hypoxia.…”
Section: Anesthetic Side-effectsmentioning
confidence: 99%